UPAYA PEMERINTAH KOTA BATAM DALAM MEMBINA MASYARAKAT TERKAIT PENGELOLAAN SAMPAH WILAYAH PERKOTAAN TAHUN 2020-2022 - Arya Amelia Anjani; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Due to the low participation of the community in government policies in an effort to reduce the impact of the waste phenomenon in accordance with the Batam City Regional Regulation No. 11 of 2013. One of the environmental problems what is a frightening specter for the community is the waste problem. Rubbish which is always produced every day, especially in Indonesia which has a large amount waste continues to increase from year to year because it has not been properly managed good and appropriate. The government is required to establish targeted policies as an effort to develop the community in waste management. Certainly, it will work if the community is willing to carry out every policy made and able to follow the warnings issued by the local government. This research aims to describe the efforts of the Batam City Environmental Service in fostering the community regarding waste problems and how the forms of activity are presented to the community to bridge the creation of environmental cleanliness. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. Then, the research location is at the Batam City Environmental Service Office. This researh found that with good cooperation between the government and the community, the success of the policy has been established. Among the programs created by DLH Batam City in the framework of fostering the community are the program to sort waste from home, regular waste weighing, socialization and environmental campaigns, and a waste bank. However, there are still elements that have not been implemented optimally, namely the lack of direct supervision by the government in charge of monitoring the locations where coaching is carried out. However, there are still elements that have not been implemented optimally that needs direct supervision by the government authorized to monitor locations where coaching is carried out which is a thing crucial to measure how far the policies made are capable to develop a sense of community concern for the environment. Keywords: Guidance by the Government, Authority, Policy Success